Geospatial Analysis for Delta Evolution of Jeneberang River in Makassar, South Sulawesi, Indonesia - Rohaya Langkoke (Geological Agency, 2023)
This study aims to document and to elucidate the Jeneberang River delta evolution during 1922 -2022 by analyzing the transport of sediment in and out of the river through erosion and sedimentation. The method used is a geospatial analysis of the delta and river evolution using the Dutch map of 1922 and Landsat long-term data from 1972, 1981, 1991, 2000, 2010, 2020, and 2022 by dividing once every fifty to two years, so the delta pattern changes. The data collection was done by downloading data via Landsat, the data processing was simulated using ArcGIS software, and sedimentation and erosion were estimated. This study shows that the lowest sedimentation occurred in 2002 - 2004 with an area of 6.21 ha, and the highest one in 2004 - 2006 with an area of 34.99 ha. The lowest erosion occurred in 2014- 2016 with an area of 1.08 ha, and the highest in 2006 - 2008 with an area of 22.64 ha. The evolution of the delta occurred due to landform and river migrations. Landform migration occurs gradually starting with the direction of migration relative to the north to relative to the west resulting in the formation of a delta landform with an area of 5349.42 ha. Furthermore, the development of the landform no longer leads relatively north to west, but there is still sediment migration due to tides and sediment supply from rivers resulting in a delta landform with an area of 5586.56 ha. Then landform migration is derived from the river sedimentary supply stalled to the north because of water gate construction which caused the concentration of migration lead to the southern estuary. Tides then became a major factor in the migration, but were not as intensive as before with additional formation with an area of 5655.79 ha. The meandering changes or evolution of rivers occur naturally and are influenced by human activities. The emergence of changes is divided into five periods ranging from changes in the meandering direction to the south to the sedimentation and control of erosion with the construction of sluices and reclamation. Based on the study and by using the Galloway classification, Jeneberang delta is classified as an estuarine delta that is predominantly influenced by tides (tide-dominated) during its formation Keywords: Landsat imagery, delta evolution, Jeneberang River, tide-dominated, South Sulawesi